Psychology and Catholicism contested boundaries - Kugelmann, Robert, 1948- (Cambridge ; New York : Cambridge University Press, 2011)
"In this historical study of psychology and Catholicism, Kugelmann aims to provide clarity in an area filled with emotion and opinion. From the beginnings of modern psychology to the mid 1960s, this complicated relationship between science and religion is methodically investigated. Conflicts such as the contested boundary between psychology and the Church of 'person' versus 'soul' are debated thoroughly. Kugelmann goes on to examine topics such as the role of the subconscious in explaining spiritualism and miracles; psychoanalysis and the sacrament of confession; myth and symbol in psychology and religious experience; cognition and will in psychology and in religious life; humanistic psychology as a spiritual movement. This fascinating study will be of great interest to scholars and students of both psychology and religious studies but will also appeal to all of those who have an interest in the way modern science and traditional religion coexist in our ever-changing society"--
"The science and profession of psychology emerged in the mid to late nineteenth century. In all its varieties, including "pop psychology," psychology is one of the ways that we in the contemporary world ask the questions: "Who am I?" "What sort of things are we?" "How shall I live my life?" "What makes me happy, sad, confused, anxious?" These questions arise not only in the abstract, they occur also in activities of healing, correcting, adjusting, guiding, treating, managing, counseling. Even though in many quarters, psychologists have distanced themselves from such questions - call them philosophical - the inescapable truth is that they surface in all psychologies, pure and applied"--
An introduction -- The major fault line: modernism and psychology -- Neoscholastic psychology -- Psychology as the boundary: Catholicism, spiritualism, and science -- Psychoanalysis versus the power of will -- From out of the depths: Carl Jung's challenges and Catholic replies -- Institutionalizing the relationship -- Humanistic psychology and Catholicism: dialogue and confrontation -- Trading zones between psychology and Catholicism -- Crossings.
Includes bibliographical references and index.
Print version record.
Keywords: Catholic Church -- History -- 20th century; Catholic Church; Catholic Church; Psychology and religion; RELIGION -- Philosophy; Psychology and religion; 1900 - 1999; Electronic books; History